Understanding Women's Labor Complexity in East Java: A Multidimensional Study - Misnanto, Misnanto; Restri Ayu Prabandari; Susanto (Universitas Trisakti, 2026)
Amid promises of meritocracy and rapid economic growth in East Java Province, harsh realities still affect female graduates. The majority of employed women (68.94%) work in the informal sector, and rural female workers (36.70%) often serve as unpaid family workers. Even in urban areas, most women (38.40%) remain concentrated in low-wage jobs. This study explores work readiness and systemic barriers using a mixed-method explanatory sequential approach. The quantitative phase analyzed data from 27 universities in East Java with 143 respondents using PLS-SEM via SmartPLS software, mapping relationships between individual capacity, institutional support, curriculum relevance, gender barriers, and labor market expectations. Results indicate that individual capacity and labor market expectations significantly affect work readiness, with curriculum relevance acting as a critical mediator. The qualitative phase involved in-depth interviews with 20 female graduates from East Java universities, revealing invisible pressures—social expectations, domestic burdens, and gender stereotypes—that hinder employment and career advancement. By integrating four main theoretical frameworks: Human Capital, Mismatch, Gendered Labor Market, and Ecological Systems, the study demonstrates that work readiness is not merely a skill issue but a product of a complex social, educational, and cultural ecosystem. The study provides cross-sector policy recommendations, including curriculum reform, revitalized career centers, gender-responsive training, and supportive government incentives to promote equitable employment for young women.